2016
DOI: 10.1189/jlb.3a1015-471r
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoke inhibits efferocytosis via deregulation of sphingosine kinase signaling: reversal with exogenous S1P and the S1P analogue FTY720

Abstract: Alveolar macrophages from chronic obstructive pulmonary disease patients and cigarette smokers are deficient in their ability to phagocytose apoptotic bronchial epithelial cells (efferocytosis). We hypothesized that the defect is mediated via inhibition of sphingosine kinases and/or their subcellular mislocalization in response to cigarette smoke and can be normalized with exogenous sphingosine-1-phosphate or FTY720 (fingolimod), a modulator of sphingosine-1-phosphate signaling, which has been shown to be clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 40 publications
(62 reference statements)
3
43
0
Order By: Relevance
“…PG, VG, and PG:VG had no significant effects on phagocytosis (24.5-27.66% vs. 27.01% for control). The reduction in phagocytosis in the presence of 10% CSE (8.2%) was consistent with our previous findings (Tran et al 2016;Ween et al 2016) (Fig. 2).…”
Section: E-cigarettes Cause Decreased Macrophage Phagocytic Capacitysupporting
confidence: 93%
See 2 more Smart Citations
“…PG, VG, and PG:VG had no significant effects on phagocytosis (24.5-27.66% vs. 27.01% for control). The reduction in phagocytosis in the presence of 10% CSE (8.2%) was consistent with our previous findings (Tran et al 2016;Ween et al 2016) (Fig. 2).…”
Section: E-cigarettes Cause Decreased Macrophage Phagocytic Capacitysupporting
confidence: 93%
“…The reduction in phagocytosis in the presence of 10% CSE (8.2%) was consistent with our previous findings (Tran et al. 2016; Ween et al. 2016) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Less is known on the alteration of S1P signalling and its role in mucoobstructive diseases. Previous studies by us and others indicated complex dysregulation of the S1P signalling system in COPD (and in response to cigarette smoke) involving several components and various cell types [14][15][16]. Large gaps in this field remain, especially whether and how individual components of the S1P signalling system are dysregulated in diseases such as CF, COPD, non-CF bronchiectasis, and whether mucus obstruction directly contributes to this dysregulation.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of targeting S1P in lung cancer, aside from the antibody, using SphK2 inhibitors and its combination with SphK1 inhibitors seem to be promising approaches that merit further discovery [60]. In addition, agents such as transporter Spns2 [26] have shed new insights into the biology of S1P signaling.…”
Section: Discussionmentioning
confidence: 99%